Examining video self-reflection for teaching practice / Jasmine Jain - Jain, Jasmine (UiTM Press, 2017)
There have been numerous studies looking at the use of video in recording teaching and subsequently for the video to be used for the teacher to view and reflect on. However, it was found that the framework to guide such practice for implementation is lacking and most model only resort to the traditional triad model of assessment in teaching practice. This paper acknowledge the need for pre-service teachers to be reflective in their practice and hence review the work done by other studies, specifically on the dimension of collaborative reflection, structures of reflection, length of video as well as the frequency of reflection. The review of the aforementioned dimensions subsequently led to a proposed model, namely the pentagonal model of assessment in teaching practice. With the proposed framework place in context, the discussion of how it can be implemented follows.